1994
DOI: 10.3109/08880019409141907
|View full text |Cite
|
Sign up to set email alerts
|

Returning to Primary School After Treatment for Cancer

Abstract: Questionnaires were sent to the teachers of 14 children returning to school after treatment for childhood cancer and their 11 siblings. Forty-four control children from the same classes were also selected. Behavioral rating scores (Deasy-Spinetta) showed no differences between cases and siblings or control children in terms of learning disabilities, socialization, and emotional behavior. Teachers reported few problems on the case children's return to school, although many had been anticipated. Most children ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0

Year Published

1997
1997
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 6 publications
1
8
0
Order By: Relevance
“…The finding of normal school behaviour is in agreement with the assessment of Gregory et al (1994) of 14 children returning to primary school after treatment for non-central nervous system malignancies and the series of Mulhern et al (1994) of 11 brain stem glioma survivors with adequate behavioural adjustment 1.5-5.6 years after diagnosis. In contrast, Slavc et al (1994) studied 67 children with CNS tumours, of whom 25% of the survivors had behavioural and adjustment problems and 25% attended special educational courses.…”
Section: Survivors Of Cns Tumours School Behaviour and Performancesupporting
confidence: 84%
See 1 more Smart Citation
“…The finding of normal school behaviour is in agreement with the assessment of Gregory et al (1994) of 14 children returning to primary school after treatment for non-central nervous system malignancies and the series of Mulhern et al (1994) of 11 brain stem glioma survivors with adequate behavioural adjustment 1.5-5.6 years after diagnosis. In contrast, Slavc et al (1994) studied 67 children with CNS tumours, of whom 25% of the survivors had behavioural and adjustment problems and 25% attended special educational courses.…”
Section: Survivors Of Cns Tumours School Behaviour and Performancesupporting
confidence: 84%
“…Investigation and analyses of cohorts including subjects with wide ranges of primary pathologies is likely to account, in part, for this lack of clarity. Interestingly, despite the assumed belief that survivors of central nervous system tumours are likely to experience a high overall morbidity burden, they are invariably the one group of patients excluded from studies of school behaviour, performance and health status (Eiser and Town, 1987;Allen et al, 1990; Gamis and Nesbit, 1991;Glauser and Packer, 1991;Gregory et al, 1994). Consequently even less information regarding this high-risk population of survivors exists.…”
mentioning
confidence: 99%
“…Studies have documented attendance problems and school phobia in survivors of childhood cancer, often because of a significant amount of missed school days (Williams, Ochs, Williams, & Mulhern, 1991). Treatments often change a child's appearance, stamina, and well-being that contribute to social unease and, if not appropriately addressed, may lead to school phobia (Gregory et al, 1994). Other studies have suggested that factors contributing to the high rate of absenteeism and school phobia are related to the child's sense of failure when he or she cannot perform at his or her expected level.…”
Section: Need For Specialized Servicesmentioning
confidence: 98%
“…Successful school reintegration for children diagnosed with cancer is best facilitated by a coordinated effort between and within the home, school, and hospital ecosystems; but explicit models for promoting such coordinated reintegration have been scarce (Harris, 2009). Often, school services lack the comprehensive approach to care that has been found to be so essential to the successful treatment of chronic health condition such as childhood cancer (Gregory et al, 1994;Keene, 1999;Linet et al, 1999). It is common practice for school reintegration programs to focus on getting a child with cancer mainstreamed and back into a regular educational setting.…”
Section: Need For Specialized Servicesmentioning
confidence: 99%
See 1 more Smart Citation